Investigating a manufacturing ecosystem in transition toward electric vehicles – a business model perspective - Rachinger, Michael; Müller, Julian (Journal of Manufacturing Technology Management, 2024)
Purpose: Business Model Innovation is increasingly created by an ecosystem of related companies. This paper aims to investigate the transition of a manufacturing ecosystem toward electric vehicles from a business model perspective. Design/methodology/approach: The authors investigate an automotive manufacturing ecosystem that is in transition toward electric and electrified vehicles, conducting semi-structured interviews with 46 informants from 27 ecosystem members. Findings: The results reveal that the actions of several ecosystem members are driven by regulations relating to emissions. Novel requirements regarding components and complementary offers necessitate the entry of actors from other industries and the formation of new ecosystem members. While the newly emerged ecosystem has roots in an established ecosystem, it relies on new value offers. Further, the findings highlight the importance of ecosystem governance, while the necessary degree of change in the members' business models depends on their roles and positions in the ecosystem. Therefore, upstream suppliers of components must perform business model adaptation, whereas downstream providers must perform more complex business model innovation. Originality/value: The paper is among the first to investigate an entire manufacturing ecosystem and analyze its transition toward electric vehicles and the implications for business model innovation.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Automotive industry; Business model innovation; Case study; Electric vehicles; Electrification; Manufacturing ecosystem